2014
DOI: 10.1186/1756-0500-7-826
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of tendon markers in mesenchymal stromal cells derived from different sources

Abstract: BackgroundMultipotent mesenchymal stromal cells (MSC) can be recovered from a variety of tissues in the body. Yet, their functional properties were shown to vary depending on tissue origin. While MSC have emerged as a favoured cell type for tendon regenerative therapies, very little is known about the influence of the MSC source on their properties relevant to tendon regeneration.The aim of this study was to assess and compare the expression of tendon extracellular matrix proteins and tendon differentiation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 32 publications
1
36
1
Order By: Relevance
“…In the current study, DCN overexpression was found in both TNMD+ and unsorted hASCs. This outcome is in agreement with the fact that DCN is relatively higher in hASCs than in MSCs from other sources and in native tendon (Burk et al, ). DCN increases from 14 to 28 days in TNMD+ subpopulations cultured in basal and PDGF‐BB media ( p < 0.01 and p < 0.001 respectively).…”
Section: Resultssupporting
confidence: 90%
“…In the current study, DCN overexpression was found in both TNMD+ and unsorted hASCs. This outcome is in agreement with the fact that DCN is relatively higher in hASCs than in MSCs from other sources and in native tendon (Burk et al, ). DCN increases from 14 to 28 days in TNMD+ subpopulations cultured in basal and PDGF‐BB media ( p < 0.01 and p < 0.001 respectively).…”
Section: Resultssupporting
confidence: 90%
“…Other study using AdMSCs suspended in PC also showed increased tendon vascularization through power Doppler analysis after six weeks of therapy (CARVALHO et al, 2013a). Such increased tendon vascularization may favor tissue repair, since poor vascularization is one of the explanations for the slow tendon repair and for the formation of a biomechanically inferior MSC (GONÇALVES et al, 2013;BURK, 2014).…”
Section: Svf and Admscs In The Equine Tendinitis Treatmentmentioning
confidence: 95%
“…The AdMSCs were those with greater type I and III collagen and decorin expression. Once the improvement in the cellular matrix has been pointed as the main beneficial effect of the cellular therapy against tendinitis, the use of adipose tissue as stem cell source may result in therapeutic effect better than that of other sources, since it has greater protein expressions such as type I collagen (BURK et al, 2014).…”
Section: What Is the Best Source To Be Used Adipose Tissue Or Bone Mmentioning
confidence: 99%
“…69 Other cell sources, such as synovial membrane-derived MSCs may provide advantages for joint-based therapies, but are not yet extensively studied in the horse. 83 Burk et al 84 investigated the gene expression of tendon markers from different MSC sources including bone marrow-derived MSCs, adipose-derived MSCs, umbilical cord tissue-derived MSCs, and MSCs from umbilical cord blood; the study concluded that adiposederived MSCs may be more appropriate for the treatment of tendon lesions as they demonstrate the highest expression of collagen 1A2, collagen 3A1, and decorin. The earlier outlined literature suggests bone marrow-derived MSCs may be more appropriate for cartilage or bone healing, and adipose-derived MSCs may be more phenotypically appropriate for tendon lesions.…”
Section: Clinical Considerationsmentioning
confidence: 99%